New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae) - Soto-Hernández, Macotulio (Zootaxa, 2017)
Four new species of the previously monotypic genus Narberdia Burke are described. All of them are intimately associated with plants of the genus Bernardia (Euphorbiaceae). Narberdia cervantae Soto-Hernández, new species (México, Jalisco on Bernardia spongiosa McVaugh), N. sarukhani Soto-Hernández, new species (México, Veracruz and Costa Rica on B. mexicana (Hook. & Arn.) Müll. Arg. and B. nicaraguensis Standl. & L.O. Williams), N. dugesi Soto-Hernández (México, Querétaro and Michoacán on B. mexicana and B. albida Lundell), and N. ramuvei Soto-Hernández, new species (México, Durango, Jalisco and Puebla on B. changii A. Cerv. & Flores Olv., B. rzedowskii A. Cerv. & Flores Olv. and B. valdesii A. Cerv. & Flores Olv.). Use of more than one species of plant as a host by one species of weevil is a common occurrence in Anthonomini. Sexual dimorphism is evident in the species with the female rostrum more slender and relatively longer than in male, the antennal scape attached near the midpoint of the rostrum in the female and beyond the midpoint in the male, and female with pro- and mesotibia bearing a tooth adjacent to the mucro, this tooth absent in the male. Specimens were collected at elevations from 62 m to 2288 m. The genus, previously only known from the United States of America and extreme northern México is now also known from Costa Rica as well as other areas of México. Narberdia apparently is most closely related to several Anthonomus squamosus species group members, both with similar characters of the body and form of the male median lobe (broad at the apex and strongly narrowed near the apex).